Fenologia e morfologia de plantas e biometria de frutos e sementes de muricizeiro (Byrsonima verbascifolia (L.) Rich.) do tabuleiro costeiro de Alagoas - Araújo, Rychardson Rocha de (2009)
Muricy (Byrsonima verbascifolia (L.) Rich.) is distinguished as a tropical fruit species of ample distribution in the Cerrados and coastal plains of Brazil. Even though its botanical importance and economic potential, very few studies have been carried out with this species that lacks knowledge in relation to its physiological and phenological behavior. The objective of this work was to study the phenology and morphology of plants, fruits and seeds of twenty native adult plants in a natural coastal plain area of the state of Alagoas. All selected plants had presented a clear synchronism in all studied phenophases. The leaves abscission of the plants occurred all throughout the studied period, but it was more intense in the driest months of the year (September to November) and was always followed by the sprouting of new leaf buds and flowers. On the other hand, the fruit production was concentrated mainly between December and February. Reproductive phenophases in the plants showed to be dependent on the environment where they grew, since the same species studied in other regions presented different reproductive periods. The correlation between the main morphometric indices of the plants canopy (total height of the plant, diameter, length and ratio of canopy) indicated that they were positively correlated with the diameter of the stem at the ground level. The total height was only positively correlated with the diameter and length of the canopy. The biometric analyses showed that the mean weight of the fresh fruits was of 1.21 g, the longitudinal diameter and the transversal line of the fruits were, respectively, 8,5 millimeters and 7,4 millimeters, and the mean proportion of the pulp was of 63%. The mean fresh mass of the fruits was proportional to the amount of pulp (r = 0.605; P < 0.05), indicating an interesting potential for future works of plant improvement in this species.